2016
DOI: 10.1088/0029-5515/56/5/056011
|View full text |Cite
|
Sign up to set email alerts
|

ELM behaviour and linear MHD stability of edge ECRH heated ASDEX Upgrade plasmas

Abstract: Abstract. In order to test the peeling-ballooning ELM model, ECRH heating was applied to the edge of ASDEX Upgrade type-I ELMy H-mode plasmas to alter the pedestal pressure and current density profiles. The discharges were analysed with respect to ideal MHD stability. While the ELM frequency increased and the pedestal gradients relaxed with edge ECRH, the MHD stability boundary did not change. The results indicate that the peeling-ballooning model is insufficient to fully explain the triggering of ELM instabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The goal of the experiments presented in this section is to test whether an edge deposition of the ECRH power has an impact on the behaviour of the plasma profiles during the ELM cycle and on the ion heat transport. Previous experiments on AUG showed that the application of edge ECRH heating affected the ELM frequency and caused a small relaxation of the edge gradients, while the MHD stability boundary remained unchanged [23]. A second, higher frequency ELM band appeared when depositing more ECRH power to the edge.…”
Section: On-and Off-axis Ecrh Heatingmentioning
confidence: 86%
See 1 more Smart Citation
“…The goal of the experiments presented in this section is to test whether an edge deposition of the ECRH power has an impact on the behaviour of the plasma profiles during the ELM cycle and on the ion heat transport. Previous experiments on AUG showed that the application of edge ECRH heating affected the ELM frequency and caused a small relaxation of the edge gradients, while the MHD stability boundary remained unchanged [23]. A second, higher frequency ELM band appeared when depositing more ECRH power to the edge.…”
Section: On-and Off-axis Ecrh Heatingmentioning
confidence: 86%
“…As shown in figure 1, at these medium density levels the edge ECRH has hardly an impact on the plasma parameters, including the ELM frequency. Note that in [23] the deposition location could be moved even further towards the plasma edge, i.e. ρ ≈ 0.88 pol .…”
Section: On-and Off-axis Ecrh Heatingmentioning
confidence: 99%
“…On the other hand, it has been seen earlier in TCV that the ELM frequency has increased by a factor of 2 and the energy loss per ELM is reduced by the same factor when ECH deposition is shifted to the pedestal region from well inside the plasma boundary, while keeping the total input power constant [32]. When ECH is applied at the edge of AUG plasmas, the ELM frequency increased, and pedestal gradients relaxed without changing the MHD stability boundary [34]. Hence, 'how long' the inter-ELM period will be and 'why' for a given heating scenario, are still unresolved issues for the pedestal.…”
Section: Introductionmentioning
confidence: 93%
“…The MHD stability is parameterized here in terms of the maximum normalized edge pressure gradient α max [39] and flux-surface averaged edge current density j tor . The lines show the stability boundary defined with the criterion used in [40] for both I-mode and H-mode. Above the stability boundary, peelingballooning modes are unstable and type-I ELMs occur.…”
Section: Mhd Stabilitymentioning
confidence: 99%